2017
DOI: 10.1051/0004-6361/201730716
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved images of reactive ions in the Orion Bar

Abstract: We report high angular resolution (4.9 × 3.0 ) images of reactive ions SH + , HOC + , and SO + toward the Orion Bar photodissociation region (PDR). We used ALMA-ACA to map several rotational lines at 0.8 mm, complemented with multi-line observations obtained with the IRAM 30 m telescope. The SH + and HOC + emission is restricted to a narrow layer of 2 -to 10 -width (≈800 to 4000 AU depending on the assumed PDR geometry) that follows the vibrationally excited H * 2 emission. Both ions efficiently form very clos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(88 citation statements)
references
References 37 publications
8
80
0
Order By: Relevance
“…The thermal pressure derived in this work is of the order of magnitude 10 8 K cm −3 across our FOV, with the highest values found at the dissociation front in the Car I-E region. Although the spatial resolution of our observations prevents us from obtaining a detailed cloud structure at the dissociation front, our results are in general agreement with the recent ALMA observations of the Orion Bar that the observed cloud edge is compressed by a highpressure (2 × 10 8 K cm −3 ) wave propagating into the molecular cloud (Goicoechea et al 2016;Goicoechea et al 2017). 5.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The thermal pressure derived in this work is of the order of magnitude 10 8 K cm −3 across our FOV, with the highest values found at the dissociation front in the Car I-E region. Although the spatial resolution of our observations prevents us from obtaining a detailed cloud structure at the dissociation front, our results are in general agreement with the recent ALMA observations of the Orion Bar that the observed cloud edge is compressed by a highpressure (2 × 10 8 K cm −3 ) wave propagating into the molecular cloud (Goicoechea et al 2016;Goicoechea et al 2017). 5.…”
Section: Resultssupporting
confidence: 90%
“…Based on the non spatially-resolved CO observations from J = 4 − 3 up to J = 19 − 18 in NGC 7023 and up to J = 23 − 22 in the Orion Bar, as well as other atomic and molecular lines, and their comparisons with the Meudon PDR code (Le Petit et al 2006), it is suggested that the FUV radiation field produced by the Trapezium stars cluster and HD 200775 are responsible for a high pressure layer (P ∼10 8 K cm −3 ) at the very edge of the two PDRs and is sufficient to support the high-J CO excitation observed in the two objects (Joblin et al 2018). These results are in resonance with the recent ALMA observations which confirm the presence of a thin layer with high pressure at the edge of the PDR in the Orion Bar (Goicoechea et al 2016;Goicoechea et al 2017). More studies as such with detailed PDR modeling are necessary for understanding the excitation of CO in the interstellar environment.…”
Section: Introductionsupporting
confidence: 83%
“…The new models yield column densities that are a factor of four higher than those obtained with the previous formation and destruction rate constants (Zanchet et al 2013a). The new fractional abundances of SH + are within the uncertainties of the SH + column densities inferred from observations (Goicoechea et al 2017).…”
Section: Discussionsupporting
confidence: 67%
“…(e.g., Goicoechea et al 2016Goicoechea et al , 2017. Photoevaporation by strong UV radiation fields from young stars is considered to play a critical role in maintaining such high pressure at the edge of PDRs (e.g., Bron et al 2018).…”
Section: Strategy For Pdr Modelingmentioning
confidence: 99%